Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. Defensive silence as a mediating variable Between Organizational Trust and Work Alienation " A Field Study on Aleppo Public Banking Sector" Mrs. Ayam Ibrhm Alabed 2. The impact of administrative control on the performance of employees: An applied study on the Islamic insurance company Dr. Mutaz Mohamed Sorkaty , Dr. Ayman Sidahmed Mokhtar 3. Medical tourism based on natural ingredients and health structures as one of the solutions to obilize economic resources Co-Prof. Slim Bourchid Abdelkader , Asst-Prof. Elsiddig Yousif Mohammed Mousa 4. The reality of the implementation of national integrity standards in public sector by the council of common services of Irbid as perceived by the council staff Dr. Sabrey Radi Ali Daradkah 5. The Role of Administrative Performance in Customer Service in Achieving Satisfaction and Belonging to Commercial Dealers A field study on the grain mills sector in Sudan Dr. Sara Suliman Alawad Mudwi, Dr. Reda Abdelfattah Ibrahim Mohamed 6. The relationship between transformational leadership and entrepreneurial performance: A study on a sample of service sector institutions of Khartoum State 2022 Dr. Hassan Abdelrahmim Fadul Mohamed , Co-Prof. Elsheikh Mohammed Elkhidir Mohammed, Dr. Anis Mohammed Souissi , Dr. Huthayfah Hadi Madkhali 7. The Applying Islamic Financial Accounting Standards and Its role in Raising The Creditworthiness of Islamic Financial Institutions: A field Study on A sample of Sudanese Banks Dr. Sondous Abdalaziz Alshami , Dr. Abdelrahim Mahgoub Ahmed Mohammed , Dr. Maha Mosa Mohammad Salama , Prof. Yasir Tajelssir Mohammed Sanad , Dr. Elhadi Mekki Mawan Somij 8. Factors affecting saving in Sudan during the period 2008-2018 Dr. Minas Abdelrahman Ali Alkhabir